Mother-to-infant transmission of the carcinogenic colibactin-producing bacteria - Yuta Tsunematsu (BMC Microbiology, 2021)
Abstract Background The Escherichia coli strain that is known to produce the genotoxic secondary metabolite colibactin is linked to colorectal oncogenesis. Therefore, understanding the properties of such colibactin-positive E. coli and the molecular mechanism of oncogenesis by colibactin may provide us with opportunities for early diagnosis or prevention of colorectal oncogenesis. While there have been major advances in the characterization of colibactin-positive E. coli and the toxin it produces, the infection route of the clb + strain remains poorly characterized. Results We examined infants and their treatments during and post-birth periods to examine potential transmission of colibactin-positive E. coli to infants. Here, analysis of fecal samples of infants over the first month of birth for the presence of a colibactin biosynthetic gene revealed that the bacterium may be transmitted from mother to infant through intimate contacts, such as natural childbirth and breastfeeding, but not through food intake. Conclusions Our finding suggests that transmission of colibactin-positive E. coli appears to be occurring at the very early stage of life of the newborn and hints at the possibility of developing early preventive measures against colorectal cancer.